Refleksi Kekerasan Seksual dan Pemaksaan Seksual terhadap Perempuan: Perspektif Hukum Positif dan Hukum Islam - hartanto, hartanto; Praiseda , Fifink Alviolita (DIKTUM: Jurnal Syariah dan Hukum, 2022)
Crime in general and sexual violence are deviations from a person's good and bad morals. The author examines the factors that influence the occurrence, as well as the causes of sexual coercion and/or sexual violence in society. Sexual violence/harassment is an iceberg phenomenon, this is allegedly due to the lack of comprehensive handling from the government, the existence of unequal power relations, the lack of education about sex and social ethics in the current era of promiscuity. Sexual violence that often occurs in the society is detected in several forms/modes including threats (non-physical) to rape (physical). The study in writing this scientific paper is about the treatment and prevention in the study of sexual violence and sexual coercion in the community based on the TPKS Law. Study uses descriptive normative method, then a statutory approach, and conceptual. In the past, before the TPKS Law, sexual crimes were still very limited in terms of terminology, but now it has become wider/religious to adapt to the development of the societies sense of justice. The normative perspective of this law is quite good, so it is hoped that its implementation in the society can actually fulfill a sense of justice. In the perspective of Islamic law, through “takzir” which is seen as a punishment in Islamic criminal law, the perpetrator can be punished and the matter is handed over to the ruler or judge who has the right to decide a matter to obtain justice.